2014
DOI: 10.4186/ej.2014.18.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling of Induction Period of the Olefins Hydroalumination Reaction by Diisobutylaluminiumchloride Catalyzed with Cp2ZrCl2

Abstract: Abstract.Method of mathematical modeling of induction period for reaction of olefins hydroalumination by alkylalanes in presence of Cp2ZrCl2 was developed. The kinetic model of reaction of olefins hydroalumination by alkylalanes with presence the catalyst Cp2ZrCl2 was built. The values of kinetic parameters of reaction of olefins hydroalumination by alkylalanes in presence of Cp2ZrCl2 which describes well an experimental data were determined. Obtained values are allowed to describe an induction period in all e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 5 publications
0
6
0
1
Order By: Relevance
“…Previously, we demonstrated that, in the presence of complex 1a , at a reactant molar ratio 1a :OAC:alkene of 1:60:50, the highest hydroalumination rate among the chosen OACs was observed for AlBu i 3. In the case of ClAlBu i 2 , a long-term induction period (up to 3 h) was found . Diisobutylaluminum hydride showed the lowest activity among the studied OACs (Figure a).…”
Section: Resultsmentioning
confidence: 93%
“…Previously, we demonstrated that, in the presence of complex 1a , at a reactant molar ratio 1a :OAC:alkene of 1:60:50, the highest hydroalumination rate among the chosen OACs was observed for AlBu i 3. In the case of ClAlBu i 2 , a long-term induction period (up to 3 h) was found . Diisobutylaluminum hydride showed the lowest activity among the studied OACs (Figure a).…”
Section: Resultsmentioning
confidence: 93%
“…The corrosion rate can be affected by controlling the process kinetics in the case of electrochemical corrosion. Determination of the optimal conditions from the kinetic model of the process [17][18][19] can provide control over the phenomenon. Yan Yun Hui presented another method for identification of metal corrosion damage based on the minimum distance between the recognition objects [20].…”
Section: Computer Vision Methods and Goalsmentioning
confidence: 99%
“…Furthermore, three reactions with organoaluminum compounds (OACs) have identical steps themselves. That is why for the solution of an inverse problem, it is necessary to take into account the fact that the values of the kinetic parameters at these steps must be identical [38,39].…”
Section: Kinetic Model Of a Metal Complex Catalytic Reactionmentioning
confidence: 99%